Exploring structural features of folded peptide architectures in the construction of nanomaterials. Issue 61 (11th July 2016) - Misra, Rajkumar; Reja, Rahi M.; Narendra, Lagumaddepalli V.; George, Gijo; Raghothama, Srinivasarao; Gopi, Hosahudya N.
Abstract : Supramolecular assemblies of conformationally biased α, γ-hybrid peptides composed of alternating α-Phe and 4, 4-dimethyl substituted γ-amino acids are investigated. Abstract : We are reporting the influence of foldamer structures on their self-assembled architectures. In a sharp contrast to the ordered α, γ-hybrid 12-helix obtained from 1 : 1 alternating Aib and γ-Phe, the α, γ-hybrid peptides constituted with α-Phe and 4, 4-dimethyl γ-amino acid (Aic) displayed the extended sheet type of conformations in solution and spontaneously self-assembled into thermally and proteolytically stable capsules. In contrast, the conformationally ordered 12-helix self-assembled into a three-dimensional supramolecular polyhedron.